Rhabdomyolysis Secondary to Quadriparesis due to BrainEdema Associated with Intracranial Mass Lesions - Gurel, Alı; Genç, Fatih; Balgetir, Ferhat (My University, 2021)
Introduction: Rhabdomyolysis is a complex medical condition that develops as a result of therelease of damaged skeletal muscle cell contents into the circulation and sometimes has life threatening consequences. Trauma, drugs, toxins, infections, metabolic abnormalities, heat-relatedconditions, prolonged inactivity and excessive exercise may be among the causal factors. Case Report: We present an elderly female patient who developed rhabdomyolysis due to a rarereason: Rhabdomyolysis secondary to acute quadriparesis secondary to brain edema associatedwith intracranial mass lesions. Conclusion: Rhabdomyolysis may be a rare complication due to acute quadriparesis resultingfrom neurological pathologies. Since rhabdomyolysis can have life-threatening consequences,early diagnosis and treatment by clinicians is important.
Keywords: Genel ve Dahili Tıp; Patoloji; Nörolojik Bilimler